INTERNATIONAL MIGRATION AND POPULATION CHANGES IN MOLDOVA - TABAC, Tatiana (Economy and Sociology, 2021)
The article focuses on analyzing the implications of international migration on changes in the number and structure of the population in Moldova in the 2014-2020 period. The paper is based on revised data on the population with habitual residence and international migration. The research methodology consists of estimating and analyzing specific indicators of migration and population: emigration and immigration rates, gross and net migration rates, age specific net migration rates by sex, population growth rate and others. Results show that the emigration rate during this period increased from 43 to 58 emigrants per 1000 population. The cumulative negative net migration is -221.3 thousand people or -7.71% of the population of 2014. The level of mobility of Moldova's population is higher than that of the population of Moscow or Luxembourg. The share of women involved in the migration process is lower than that of men. Youth (aged 20-34) make up a third of the annual flow of emigrants, while return migration increases at pre-retirement ages. At the same time, there is an increase in the number of children involved in international migration, which indicates the increase in migration of families to establish residence abroad. The population of Moldova decreased by -225.3 thousand people in 2014-2020 or by 7.9%. The population decline rate varies between 0.9-1.8% annually. The article concludes that the most important contribution to population decline is negative international migration. Population decline remains the biggest demographic challenge for Moldova.